E-Commerce dalam Hukum Islam: Studi Analisis Atas Pandangan Abdul Halim Barkatullah dan Teguh Prasetyo - Ummal Khoiriyah (Program Pascasarjana Universitas Ibrahimy, 2018)
The one phenomenon of economic Mu'amalah is buying and selling transactions that use electronic media. Trading activities through internet media is popularly called electronic commerce (e-commerce). E-commerce is divided into two segments, they are business to business e-commerce and business to consumer e-commerce. This study discusses and analyzes e-commerce of Islamic Law (Analysis Study on the views of Abdul Halim Barkatullahlah and Teguh Prasetyo in a Book entitled